Study of Seasonality Tourism in Simanindo Sub-district, Samosir Regency - Dwi Debora Sitanggang (Talenta Publisher, 2021)
Abstract. Seasonal tourism is a phenomenon characterized by a determinative influence on the tourism industry. This phenomenon is not easy to solve or modify because it has related to tourist arrivals. The number of tourist arrivals is an important point because this is a source of income and revenue for the tourism industry. This study aims to understand and identify seasonal tourism that often occurs every year. The components or variables in this research measure level of tourist visits and the efforts to increase tourist visits outside the season. This research uses quantitative methods and qualitative methods. The data collection are consisted of: qualitative methods with data collection from observations, interviews, and questionnaires and quantitative methods by collecting data from agencies, books, and literature studies. The results are the peak season in the Simanindo sub-district originates from the influence of holidays or religious celebrations. The low season of tourism is caused by weather factors and human disasters. The seasonal pattern for the last three years has the same pattern. The government needs to improve the facilities and creates alternative activities during the low tourist season. The questionnaire's results from tourists satisfied with the tourism industry, infrastructure, and employment services.